2011
DOI: 10.1186/scrt79
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of human umbilical cord blood-derived mesenchymal stem cells after intrathecal administration by lumbar puncture in a rat model of cerebral ischemia

Abstract: IntroductionStem cell transplantation is a promising therapeutic strategy for the treatment of stroke. Mesenchymal stem cells (MSCs) are a potential cell source for clinical application because they can be easily obtained and cultivated with a high proliferative capacity. The safety and efficacy of cell therapy depends on the mode of cell administration. To determine the therapeutic potential of intrathecal administration of MSCs by lumbar puncture (LP), we administrated human umbilical cord blood-derived MSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
84
0
7

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 40 publications
0
84
0
7
Order By: Relevance
“…Therefore, the elucidation of potential mechanisms is vital for the further development of stem cell therapy techniques and, ultimately, their translation to the bedside. A number of proposed mechanisms have been investigated in preclinical cerebral ischemia models, including the formation of new neuronal circuitry, reduced apoptosis, promotion of angiogenesis, neurogenesis, and other endogenous www.nature.com/aps Zhu Y et al Acta Pharmacologica Sinica npg repair processes [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the elucidation of potential mechanisms is vital for the further development of stem cell therapy techniques and, ultimately, their translation to the bedside. A number of proposed mechanisms have been investigated in preclinical cerebral ischemia models, including the formation of new neuronal circuitry, reduced apoptosis, promotion of angiogenesis, neurogenesis, and other endogenous www.nature.com/aps Zhu Y et al Acta Pharmacologica Sinica npg repair processes [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies report a lowering of deficits as assessed by the composite modified neurological severity score (mNSS), while others demonstrated reduced inflammation and apoptosis, as well as increased neurite outgrowth and plasticity [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Interestingly, recent studies have also determined that exosomes secreted by MSCs are capable of inducing functional recovery in models of ischemic stroke [24,41,47,55,58].…”
Section: Mscs In the Treatment Of Ischemic Strokementioning
confidence: 99%
“…Many, but not all, of these studies reported MSCs reduced infarct size and induced functional recovery as reported by lessening of motor deficits or special learning as measured by the radial maze test [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Many of these studies report a lowering of deficits as assessed by the composite modified neurological severity score (mNSS), while others demonstrated reduced inflammation and apoptosis, as well as increased neurite outgrowth and plasticity [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57]. Interestingly, recent studies have also determined that exosomes secreted by MSCs are capable of inducing functional recovery in models of ischemic stroke [24,41,47,55,58].…”
Section: Mscs In the Treatment Of Ischemic Strokementioning
confidence: 99%
“…In many studies, different routes have been tested, including intrastriatal (11), intracerebral (12), intraventricular (13), and intrathecal by lumbar puncture (14). However, these techniques raise the possibility of additional trauma from transplantation surgery and are often impractical for patients with clinically serious conditions.…”
Section: Introductionmentioning
confidence: 99%